Development of a Salmonella cross-protective vaccine for food animal production systems. Issue 1 (1st January 2015) - Heithoff, Douglas M.; House, John K.; Thomson, Peter C.; Mahan, Michael J.
Highlights: Development of a Salmonella cross-protective vaccine for livestock production. Salmonella dam vaccines are safe in the animal and the environment. Second generation Salmonella dam vaccines exhibit improved safety. Abstract: Intensive livestock production is associated with increased Salmonella exposure, transmission, animal disease, and contamination of food and water supplies. Modified live Salmonella enterica vaccines that lack a functional DNA adenine methylase (Dam) confer cross-protection to a diversity of salmonellae in experimental models of murine, avian, ovine, and bovine models of salmonellosis. However, the commercial success of any vaccine is dependent upon the therapeutic index, the ratio of safety/efficacy. Herein, secondary virulence-attenuating mutations targeted to genes involved in intracellular and/or systemic survival were introduced into Salmonella dam vaccines to screen for vaccine candidates that were safe in the animal and the environment, while maintaining the capacity to confer cross-protective immunity to pathogenic salmonellae serotypes. Salmonella dam mgtC, dam sifA, and dam spvB vaccine strains exhibited significantly improved vaccine safety as evidenced by the failure to give rise to virulent revertants during the infective process, contrary to the parental Salmonella dam vaccine. Further, these vaccines exhibited a low grade persistence in host tissues that was associated with reduced vaccine shedding, reduced environmental persistence, and induction of cross-protective immunity to pathogenic serotypes derived from infected livestock. These data indicate that Salmonella dam double mutant vaccines are suitable for commercial applications against salmonellosis in livestock production systems. Reducing pre-harvest salmonellae load through vaccination will promote the health and productivity of livestock and reduce contamination of livestock-derived food products, while enhancing overall food safety.